The cognitive impairment illustrated in drawings used in gaining insight and motivation in alcoholism treatment - Mandić-Gajić Gordana (Vojnosanitetski Pregled)
Introduction. The neuropsychological impairment such as different severity of executive deficit and mnestic disturbance among chronic alcoholics is frequent, but usually not explored. Case report. Two clinical vignettes of alcoholics who were not simultaneously treated in day hospital are presented, and they illustrated similar visuospatial impairments in free association drawings of a house made by. In this paper, the focus was on drawing not only as diagnostic tool, but also as a means of a confrontation within the group. Qualitative analysis of drawings and protocols from the group analysis were applied in the integrative day program. After confrontation, one alcoholic increased the insight into his cognitive impairment and strengthened motivation for early abstinence and treatment maintenance. He continued drawing houses as a theme of the following sessions till his obvious visuospatial impairments were repaired. Thus, he spontaneously trained his executive abilities and got group support for their improvement. Conclusion. Drawing could be a simple means of illustration cognitive impairments and the group analysis of drawings may serve as useful adjuvant method of strengthening insight and motivation for abstinence and treatment maintenance with documented cognitive recovery during abstinence.